2019
DOI: 10.3389/fphys.2019.01045
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression and Regulation of Urotensin I and Corticotropin-Releasing Hormone Receptors in Ovary of Olive Flounder Paralichthys olivaceus

Abstract: Urotensin I (UI), a fish corticotropin-releasing hormone (CRH) like peptide, has been found throughout vertebrate species that has great effects on adaptive physiology comprising stress-related responses, and osmotic regulation by binding with CRH type I receptor (CRHR1) and CRH type II receptor (CRHR2) in fish. Dynamic expression and regulation of UI and CRH receptors in the olive flounder ovarian follicle were studied so as to make further efforts to understand the role of UI in the development of teleost ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We followed the histological procedures reported in previous studies (Zhou et al, 2019). To be briefly, ovarian tissues were placed into Bouin's fixative for 24 h, after dehydrated in ascending concentration of alcohol, cleared in xylene, the ovarian tissues were embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the histological procedures reported in previous studies (Zhou et al, 2019). To be briefly, ovarian tissues were placed into Bouin's fixative for 24 h, after dehydrated in ascending concentration of alcohol, cleared in xylene, the ovarian tissues were embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…CRHR expressions changed during ovarian development in the olive flounder (Zhou et al, 2019) and in the zebrafish (Zhou et al, 2021). In addition, treatment with 17 a, 20 b-dihydroxy-4-pregnen-3-one (DHP) increases CRHR1 mRNA expression in ovarian follicles from olive flounder (Zhou et al, 2019), and the two CRH identified in the zebrafish, decrease estradiol release from primary cultures of follicular cells in this species (Zhou et al, 2021). These data suggest a potential involvement of CRH system in teleost reproduction.…”
mentioning
confidence: 89%
“…Therefore, a deep understanding of the signaling and functional mechanisms of the CRH/CRHR1 system needs to be developed in teleosts. Scientists have elucidated the molecular properties of CRHR1 in teleost fish, such as the gene structural characters of the receptor in Cyprinus carpio (Huising, 2004;Manuel et al, 2014), protein structure and functions of the receptor in Astatotilapia burtoni (Chen and Fernald, 2008), and distribution profiles of the receptor in the ovary of Paralichthys olivaceus (Zhou et al, 2019), Fugu (Cardoso et al, 2003), and chum salmon (Pohl et al, 2001). CRHR expressions changed during ovarian development in the olive flounder (Zhou et al, 2019) and in the zebrafish (Zhou et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation